Optimalisasi Lingkungan Kerja Fisik pada PT Soechi Lines Tbk - Amandha Dwiputrie Aprilia; Marsofiyati Marsofiyati; Maulana Amirul Adha (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to understand the optimization of the physical work environment in the Finance Division of PT Soechi Lines Tbk. This study uses a qualitative approach with a descriptive case study method. Data collection techniques were carried out through observation, interviews, and documentation involving three informants who have direct involvement in the use and management of the physical work environment in the Finance Division of PT Soechi Lines Tbk. The results indicate that the condition of the physical work environment in general has supported daily administrative work activities through the availability of work facilities, open workspace layout, and regular facility maintenance carried out by the company. However, there are still several conditions that need to be considered, such as work area density, archive space management, natural lighting, and room temperature distribution. Based on the results, it can be concluded that the optimization of the physical work environment has been carried out through the provision of work facilities, facility maintenance, and arrangement of workspace layout according to the company's operational needs, but further development is still needed to create a more comfortable and organized work environment.